Математическая модель гидродинамических характеристик элементов проточной части радиально-осевой гидротурбины. Часть 1 - Мараховский, Михаил Борисович; Гасюк, Александр Иванович (НТУ "ХПИ", 2018)
Предложена математическая модель сопротивления в безразмерной полиноминальной форме, описывающая поведение коэффициентов отдельных видов потерь в зависимости от режимных параметров гидротурбины и геометрических параметров проточной части. Форма представления модели удобна, как для проведения численного исследования влияния геометрических параметров проточной части, так и проведения оптимизационных расчетов. Модель позволяет исследовать влияние отдельных видов потерь на гидродинамические характеристики проточной части радиально-осевой гидротурбины.

The article proposes a mathematical model of resistance in a dimensionless polynomial form, describing the behavior of the coefficients of individual types of losses, depending on the regime parameters of the turbine and the geometric parameters of the flow section. The model provides for the separation of losses into: profile, shock, end, edge, losses from the axial vortex. The form of representation of the model is convenient, both for carrying out a numerical study of the influence of geometric parameters of the flowing part, and for carrying out optimization calculations. The model makes it possible to investigate the effect of certain types of losses on the hydrodynamic characteristics of the flowing part of a radial-axial hydraulic turbine. It is possible to construct a theoretical universal characteristic of a hydraulic turbine.
Mathematical model of hydrodynamic characteristics of the elements of the flowing part of the radial-axial hydroturbine
Keywords: коэффициент потерь; режимные параметры гидротурбины; модель сопротивления; коэффициенты; loss factor; resistance model